How we identify and manage patients with inadequately controlled polycythemia vera - Reiter, Andreas; Harrison, Claire N. (Current hematologic malignancy reports, 2016)
Polycythemia vera (PV) is a chronic myeloproliferative neoplasm (MPN) characterized by an overactive Janus kinase/signal transducer and activator of transcription (JAK/STAT) pathway through mutations in JAK2 exons 12 or 14 (JAK2 V617F). The dominant clinical characteristics include erythrocytosis (with or without leukocytosis/thrombocytosis), thrombotic events, and symptoms. Increased risk of mortality is mainly caused by thrombotic events and progression to post-polycythemia vera myelofibrosis (PPV-MF) or secondary acute myeloid leukemia (sAML). The most important prognostic factors include age and a history of thrombotic events, although recent evidence has indicated that leukocytosis and additional cytogenetic aberrations may also be of significant prognostic value. First-line therapies include aspirin and phlebotomies, which significantly reduce the incidence of thrombotic events and prolong survival. Cytoreductive treatment with hydroxyurea (approved) and conventional or pegylated interferon-α (effective, but not approved in many countries) is initiated for high-risk or inadequately controlled disease, e.g., uncontrolled hematocrit, leukocytosis, thrombocytosis, thrombotic events, splenomegaly, or symptoms. However, some patients may not receive initial benefit from first-line therapy or may become resistant or intolerant in due course. Although second-line treatment options are limited, clinical trials have shown the efficacy of ruxolitinib toward improving blood counts, enlarged spleen, and symptoms and potentially reducing thrombotic events. Identification of patients with uncontrolled PV is important for clinical care, as such patients have a high risk of complications, and future studies with JAK inhibitors or other agents alone or in combination are needed to test their potential to reduce rates of thrombotic events and transformation to PPV-MF or sAML.